Corrosion behavior of Ni-Al alloys beneath chlorides melt salt at 700 °C. (15th May 2019) - Guo, Lili; Yue, Yuan; Pan, T.J.; Tang, Z.F.; Liu, Wei
Highlights: Corrosion of the Ni-Al alloys is strongly accelerated by the ZnCl2 -KCl chlorides. Corrosion resistance of alloys is improved with increasing Al concentration. The effect is due to the presence of Al2 O3, retarding migration of reactants. A mechanism is described as a combination of electrochemical reaction and dissolution. Abstract: Corrosion behavior of the binary Ni- x Al alloys ( x = 6, 10, and 15 at.%) is comparatively studied in pure oxygen with and without a ZnCl2 -KCl melt deposit at 700 °C. The oxidation of all alloys in oxygen atmosphere is strongly accelerated by ZnCl2 -KCl deposits, with the formation of porous oxide scales and internal attack of the matrix induced by chlorine. The corrosion resistance of Ni-Al alloys under these present corrosion conditions is improved with increasing aluminum content of alloys, which is ascribed to the formation of alumina in the inner layer of corrosion products. The effect of aluminum is attributed to the increasing of the Al2 O3 content in the oxide scales, which may act as barrier to prevent the rapid migration of the reactants through the oxides film layer. A mechanism accounting for the accelerated corrosion of Ni-Al alloys beneath ZnCl2 -KCl deposits is regarded as a result of the combination of electrochemical reactions and active oxidation under mixed chlorides deposits.